Evaluation of different chicken layer breeds for use in integrated aquaculture-poultry production systems in Gauteng, South Africa - Van Rensburg, Connie E.J. (University of Pretoria, 2013)
Dissertation (MSc(Agric))--University of Pretoria, 2013.